The Development of Robot Malin Kundang Miniature Devices in Training Learning in Class VI Primary School - Exsaris Januar (International Journal of Educational Dynamics, 2019)
Abstract: This research originated from a problem that occurred in the sixth grade of SDN 44 Alur Tengah, North Lintau Buo Subdistrict, Tanah Datar District, West Sumatra Province, originating from the problem of lack of concrete props about explaining the eclipse process. The purpose of this study was to improve the results of learning and motivation of students in following the learning process in the field of Natural Sciences, the material for the process of eclipses. The research used ADDIE Development Research (Analysis, Design, Development, Implementation and Evaluation). Improving student learning outcomes has increased from. Before the props were applied the average learning outcomes were 68.57 and after the average teaching aids were applied the learning outcomes were 83.33. The conclusion of this research is the application of Malin Kundang Robot Miniature Props Development can improve learning outcomes and activities of class VI students of SDN 44 Alur Tengah.